Effect of Using Natural Liquid Soap on the Effectiveness of Staphylococcus Aureus Bacteria Control and Skin Health: A Review - Al Qindy, Wildan Hidayah; Septiani, Dia (Jurnal Pijar Mipa, 2024)
The skin is a protective barrier against environmental disturbances and infections. Staphylococcus aureus is a common bacterium on human skin that can lead to infections. In light of this, the study investigates the effectiveness of natural liquid soaps in controlling Staphylococcus aureus while promoting overall skin health. The primary objective is to showcase the advantages of using natural ingredients in liquid soap formulations compared to synthetic chemicals. To achieve this, the researchers conducted a systematic literature review (SLR), utilizing reputable databases such as PubMed and Mendeley to gather relevant studies focused on natural liquid soaps. They carefully selected articles based on inclusion criteria established through the PICO framework, emphasizing the antibacterial effectiveness of these natural products against Staphylococcus aureus. The review encompassed ten high-quality studies, revealing that formulations containing natural extracts such as breadfruit leaf, cardamom, aloe vera, and honey exhibited significant antibacterial activity against Staphylococcus aureus. These natural ingredients offered effective bacterial control and provided additional benefits, including skin moisturization and reduced irritation, making them preferable to synthetic alternatives. This study introduces a novel perspective by comprehensively reviewing various natural ingredients used in liquid soaps and their comparative effectiveness against Staphylococcus aureus. It underscores the potential of plant extracts and essential oils as safer and more effective alternatives to traditional chemical antibacterial agents in skin cleansers. In conclusion, natural liquid soaps effectively reduce Staphylococcus aureus on the skin while maintaining skin health. Incorporating natural ingredients ensures antibacterial protection without the adverse effects commonly associated with chemical-based soaps, such as dryness or irritation, thereby advocating a shift towards more natural skincare options.